DAMPAK PELATIHAN TERHADAP LITERASI PSAK 101 DAN 109 MAHASISWA AKUNTANSI SYARIAH UIN IMAM BONJOL PADANG - Dewi, Novia Citra; Lubis, M. Zaky Mubarak; Misneli, Misneli; Nusabil, Gery (UIN MAHMUD YUNUS BATUSANGKAR, 2024)
The problem of misappropriation of funds by philanthropic organizations is caused by the weak financial reporting based on PSAK 101 and PSAK 109.weak financial reporting based on PSAK 101 and PSAK 109. One ofone of the factors causing this is the low level of human resources who understand PSAK 101 and PSAK 109. Understand PSAK 101 and PSAK 109. This study aims to determine literacy of Islamic accounting students towards PSAK 101 and PSAK 109 and the impact of providing training on student literacy. training on student literacy. This research is a quantitative quantitative research with a sample of 54 people who meet the criteria. Data processed using the Wilcoxon signed rank test. The results showed that the literacy level of Islamic accounting students on PSAK 109 and PSAK 101 is still low before the training. training. This can be seen from the results of the pre-test whose average score is 62.22 points, with the lowest score of 20 points, which means that they can only answer 4 out of 20 questions given. Questions out of 20 questions given. The level of literacy of Islamic accounting students after being given training on PSAK 109 and PSAK 101 has increased. We can see this from the descriptive test and Wilcoxon test. At descriptive test, it can be seen that the average student score after training and posttest has increased dramatically by 90 points from training and posttest has increased dramatically by 90 points from previously the pretest average was 62.22 points. And for the highest value is 100 points. Based on the Wilcoxon test, it shows that 47 students have a higher posttest score than the pretest. This means that the training provided resulted in a higher.